The positive pharmacy care law: an area-level analysis of the relationship between community pharmacy distribution, urbanity and social deprivation in England - Todd, Adam (BMJ Publishing Group, 2014)
OBJECTIVES: To: (1) determine the percentage of the population in England that have access to a community pharmacy within 20 min walk; (2) explore any relationship between the walking distance and urbanity; (3) explore any relationship between the walking distance and social deprivation; and (4) explore any interactions between urbanity, social deprivation and community pharmacy access. DESIGN: This area level analysis spatial study used postcodes for all community pharmacies in England. Each postcode was assigned to a population lookup table and lower super output area (LSOA). The LSOA was then matched to urbanity (urban, town and fringe or village, hamlet and isolated dwellings) and deprivation decile (using the Index of Multiple Deprivation score). PRIMARY OUTCOME MEASURE: Access to a community pharmacy within 20 min walk. RESULTS: Overall, 89.2% of the population is estimated to have access to a community pharmacy within 20 min walk. For urban areas, that is 98.3% of the population, for town and fringe, 79.9% of the population, while for rural areas, 18.9% of the population. For areas of lowest deprivation (deprivation decile 1) 90.2% of the population have access to a community pharmacy within 20 min walk, compared to 99.8% in areas of highest deprivation (deprivation decile 10), a percentage difference of 9.6% (8.2, 10.9). CONCLUSIONS: Our study shows that the majority of the population can access a community pharmacy within 20 min walk and crucially, access is greater in areas of highest deprivation—a positive pharmacy care law. More research is needed to explore the perceptions and experiences of people—from various levels of deprivation—around the accessibility of community pharmacy services.